The impact of implementing the health transformation strategy on service delivery from the employees’ point of view in Kingdom of Saudi Arabia - Al-Shehri, Hassan Amer (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to assess the impact of the health transformation strategy on the provision of healthcare services from the perspective of employees in the Kingdom. The descriptive and analytical methodology was used, along with a questionnaire, to collect data from administrative staff in hospitals and healthcare centers. After analyzing the data, the study found that there is a high level of health transformation in the Kingdom across its three dimensions, and there is also a high level of healthcare service provision. The study also found a statistically significant positive correlation between the level of health transformation across its three dimensions and the level of healthcare service provision in the Kingdom. Important findings from the study include the need to improve the level of healthcare staff and provide a supportive and stimulating environment for their work, as well as improving communication with beneficiaries of healthcare services. The study recommended maintaining the Kingdom’s excellent level of healthcare services by providing all the necessary resources and requirements to achieve the goals of Vision 2030.